A Question of Identity? Purpose, Policy and Practice in the Teaching of History in Northern Ireland and the Republic of Ireland. Issue 2 (1st May 2013) - McCully, Alan; Waldron, Fionnuala
Abstract : This article traces the evolution of history education, north and south of the Irish border since partition of the island in 1921. It begins with an historical overview of the situation common across Ireland prior to partition. Subsequent developments in history provision in elementary, primary and early secondary education are traced in each of the two jurisdictions that emerged after partition, the Irish Free State, which became the Republic of Ireland, and Northern Ireland. In each case, the educational and political imperatives of each, which shaped these changes, and resulted in divergence, are identified, analysed and compared. Evidence is drawn from the dominant literature in each jurisdiction and on relevant curriculum documents. The paper concludes by demonstrating that in a post-modern, increasingly globalised world, shared educational ideas and political aspirations emerging from the Irish peace process are acting to bring the respective history curricula back into symmetry and, thereby, providing opportunities for increased co-operation.